Would Relaxation of the Anti-doping Rule Lead to Red Queen Effects?. Issue 3 (3rd July 2021) - Kayser, Bengt; De Block, Andreas
ABSTRACT: One of the claims sometimes advanced in favour of anti-doping is that allowing doping would lead to a uniform increase in performance in comparison to no doping. The idea is that if all athletes would use doping, this would just shift the playing field to a higher level without a change in ranking, but at a higher health cost. In this paper, we critique this contention. We first develop our theoretical framework, with reference to the so-called Red Queen effect. We then argue that, if doping were allowed, Red Queen effects would not be the rule. We also show that to some extent Red Queen effects would occur, but these would not necessarily be morally problematic. We end by developing an argument in favour of a more liberal approach of doping, since such would allow escaping from today's runaway effects of anti-doping efforts.